How does a β-hairpin fold/unfold? Competition between topology and heterogeneity in a solvable model - Guo, Chinlin (The National Academy of Sciences, 2000)
We study the competition between topological effects and sequence inhomogeneities in determining the thermodynamics and the un/folding kinetics of a β-hairpin. Our work utilizes a new exactly solvable model that allows for arbitrary configurations of native contacts. In general, the competition between heterogeneity and topology results in a crossover of the dominant transition state. Interestingly, near this crossover, the single reaction coordinate picture can be seriously misleading. Our results also suggest that inferring the folding pathway from unfolding simulations is not always justified.